Preparation method and application of efficient and low-consumption heterogeneous catalyst based on photo-Fenton system
By constructing the Fe3O4/UIO-66-NH2@BA heterophase catalyst with core-shell structure, combined with the photo-Fenton synergy, the problems of unrecoverable and inefficient traditional Fenton reaction catalysts are solved, efficient degradation and antibacterial effects under neutral pH conditions are achieved, and energy consumption and cost are reduced through magnetic recovery.
Patent Information
- Application Number
- CN202510329863.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-06-03
AI Technical Summary
Traditional Fenton reaction catalysts are not recyclable, have a narrow pH application range, low H2O2 utilization rate and slow Fe ion circulation rate, resulting in low efficiency and potential pollution.
The Fe3O4/UIO-66-NH2@BA heterophase catalyst adopts a core-shell structure, efficiently degrades organic pollutants under neutral pH conditions through photo-Fenton synergy, and realizes rapid recovery of the catalyst through magnetic properties.
Under the conditions of 50W LED light source and 5ml/L H2O2, the 97.3% degradation efficiency of rhodamine B and 99.10% sterilization rate of E. coli were achieved, which significantly reduced energy consumption and operating costs, while ensuring the stability and recyclability of the catalyst.
Smart Images

Figure CN120079441A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of inorganic nanomaterials and the environment, and provides a preparation method and application of a highly efficient and low-consumption heterogeneous catalyst based on a photo-Fenton system. Background Art
[0002] With the rapid development of industrialization, environmental and public health problems caused by organic dye wastewater and microbial pollution have become increasingly severe. Research shows that advanced oxidation processes (AOPs) have become one of the core technologies for water pollution treatment due to their ability to efficiently degrade organic pollutants [1]. Among them, the Fenton reaction activates H 2+ / Fe 3 through the redox cycle of Fe 2 O 2 to generate reactive oxygen species (ROS) such as hydroxyl radicals (·OH), showing important application values in wastewater treatment, antibiotic degradation, and sterilization [2]. However, the traditional homogeneous Fenton system has the following limitations:
[0003] (1) It needs to operate in an acidic environment (pH < 4), otherwise it is easy to generate Fe(OH) 3 precipitation, resulting in catalyst deactivation and difficult recovery;
[0004] (2) The Fe 2+ / Fe 3+ cycle rate is low, and the utilization rate of H 2 O 2 is insufficient;
[0005] (3) Residual transition metal ions after the reaction may cause secondary pollution [3].
[0006] To break through the above bottlenecks, heterogeneous photo-Fenton technology has gradually become a research hotspot. Heterogeneous catalysts can remain stable under neutral pH conditions and can be efficiently recovered by physical means (such as magnetic separation, filtration) [4]. At the same time, introducing external energy sources (light, sound, electricity, microwave, etc.) can accelerate the redox of Fe 2+ / Fe 3+ . In summary, using the inexhaustible solar energy as an auxiliary energy source, the heterogeneous photo-Fenton process has more development prospects.
[0007] [1]Li, J., et al., Application of α-Fe 2 O 3-Based Heterogeneous Photo-Fenton Catalyst in Wastewater Treatment: A Review of Recent Advances. Journal of Environmental Chemical Engineering, 2022. 10(5): p. 108329.
[0008] [2] Qi, J., et al., Nanomaterials-modulated Fenton reactions: Strategies, chemodynamic therapy and future trends. Chemical Engineering Journal, 2023. 466: p. 142960.
[0009] [3] Zhang, Y., et al., Weakly hydrophobic nanoconfinement by graphene aerogels greatly enhances the reactivity and ambient stability of reactivity of MIL-101-Fe in Fenton-like reaction. Nano Research, 2021. 14(7): p. 2383-2389.
[0010] [4] Clarizia, L., et al., Homogeneous photo-Fenton processes at near neutral pH: A review. Applied Catalysis B: Environmental, 2017. 209: p. 358-371. Summary of the Invention
[0011] The object of the present invention is to solve the technical bottlenecks existing in the traditional Fenton reaction, such as the non-recyclable catalyst, narrow pH applicable range (acidic environment required), low utilization rate of H 2 O 2 and slow Fe ion recycling rate. By constructing a core-shell structure of Fe 3 O 4 / UIO-66-NH 2@BA heterogeneous catalyst enables efficient degradation of organic pollutants (such as Rhodamine B) and sterilization (such as Escherichia coli) through the synergistic effect of photo-Fenton under environmental pH conditions, and at the same time, the catalyst can be rapidly recovered by means of magnetism, significantly reducing energy consumption and operating costs.
[0012] To achieve the above object, the following technical solutions are adopted:
[0013] The present invention provides a preparation method of an efficient and low-consumption heterogeneous catalyst based on a photo-Fenton system, comprising the following steps:
[0014] Step (a) Preparation of Fe 3 O 4 nanospheres: Dissolve FeCl 3 ·6H 2 O, Na 3 Cit·2H 2 O and NaOAc in a mass ratio of 1.082:(0.0516 - 0.516):1.2 in ethylene glycol, magnetically stir for 1 hour to form a uniform precursor, transfer it to a reaction kettle with a filling degree of 50 - 70%, react at 190 - 210 °C for 8 - 12 hours, cool, and separate the product by magnetic separation or centrifugation, wash and dry at 60 °C to obtain a powdery product;
[0015] Step (b) Preparation of Fe 3 O 4 / UIO-66-NH 2 @BA composite material: Disperse the Fe 3 O 4 nanospheres obtained in step (a) and ZrCl 4 in 40 ml of DMF and ultrasonicate for 15 minutes, add NH 2 -BDC and benzoic acid and continue ultrasonication for 15 minutes, transfer to a reaction kettle and react at 130 °C for 12 hours, cool, and collect the precipitate by magnetic separation or centrifugation, wash and vacuum dry to obtain Fe 3 O 4 / UIO-66-NH 2 @BA.
[0016] In the above method, the amount of ethylene glycol used in step (a) is 40 ml, the filling degree of the reaction kettle is 60%, the reaction temperature is 200 °C, and the reaction time is 10 hours.
[0017] In the above method, the mass ratio of Fe 3 O 4 , ZrCl 4 , NH 2 -BDC to benzoic acid is 1:(1.1 - 1.3):(0.8 - 1.0):(18 - 22).
[0018] The present invention also provides an Fe 3 O 4 / UIO-66-NH 2 @BA heterogeneous catalyst for use in a visible light-Fenton reaction, which is used for degrading organic pollutants or inactivating bacteria in water under a 50 W LED light source with λ≥420 nm and in the presence of H 2 O 2
[0019] Furthermore, the concentration of the H 2 O 2 is 1-20 ml / L.
[0020] Furthermore, the concentration of the H 2 O 2 is 5 ml / L.
[0021] The present invention also provides an Fe 3 O 4 / UIO-66-NH 2 @BA heterogeneous catalyst, which is composed of an Fe 3 O 4 nano-microsphere core and a UIO-66-NH 2 @BA shell layer. The thickness of the shell layer is 8-12 nm, and Zr elements are uniformly distributed in the shell layer, while Fe and O elements are concentrated in the core.
[0022] The catalyst in the above solution has enhanced absorption in the range of 400-800 nm in the ultraviolet-visible absorption spectrum, and the band gap energy is 2.33 eV.
[0023] The Fe 3 O 4 / UIO-66-NH 2 @BA (FBU) photo-Fenton heterogeneous catalyst shows the following remarkable advantages through the core-shell structure design and the photo-Fenton synergy:
[0024] 1. High catalytic degradation performance
[0025] Under a 50 W LED light source and 5 ml / L H 2 O 2 conditions, the degradation efficiency of rhodamine B (RhB) reaches 97.3% within 60 minutes, which is significantly better than that of the single-component system (Fe 3 O 4 / H 2 O 2 / light irradiation system: 30.4%; UIO-66-NH 2 @BA / H 2 O 2 / Lighting system: 47.2%).
[0026] The synergistic effect of light and H 2 O 2 is crucial: Without light (FBU / H 2 O 2 system) or without H 2 O 2 (FBU / lighting system), the degradation efficiency drops to 54.5% and 65.9% respectively, indicating that the composite system accelerates the Fe 2+ / Fe 3+ cycle through photoexcitation and improves the utilization rate of H 2 O 2 .
[0027] 2. Low consumption and optimized reaction conditions
[0028] The dosage of H 2 O 2 only needs to be 5 ml / L to achieve a 97.3% RhB degradation efficiency, while when the dosage increases to 20 ml / L, the efficiency only increases by 1.3% (reaching 98.6%), significantly reducing the reagent cost.
[0029] 3. Excellent antibacterial performance
[0030] Under the synergistic effect of a 50W LED light source and H 2 O 2 , the sterilization rate of FBU against Escherichia coli reaches 99.10% (the number of colonies decreases by 2.01 orders of magnitude), far exceeding the treatment effects of single components or single conditions (such as the weak sterilization effect of Fe 3 O 4 / H 2 O 2 or the FBU / lighting system).
[0031] 4. Wide spectral response and bandgap optimization
[0032] The FBU composite material realizes a red shift in the visible light absorption range through a core-shell structure, with a bandgap of 2.33 eV, significantly lower than that of UIO-66-NH 2 @BA (2.84 eV), and higher than that of Fe 3 O 4 (1.80 eV), balancing the light absorption and charge separation efficiency and enhancing the photocatalytic activity.
[0033] 5. Environmental friendliness and recyclability
[0034] The Fe 3 O 4 core endows the material with magnetism, enabling it to be quickly recycled through an external magnetic field, reducing catalyst loss;
[0035] The composite material operates stably under environmental pH conditions, avoiding the dependence on acidic conditions in traditional homogeneous Fenton reactions.
[0036] In summary, through the core-shell structure design and multi-component synergistic effect, the present invention achieves the simultaneous improvement of efficient pollutant degradation and antibacterial performance under low energy consumption (50W LED) and low reagent dosage (H 2 O 2 5ml / L), providing a green and sustainable solution for the water treatment field. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 : Morphology and structure characterization of the FBU heterogeneous catalyst, (a-c) SEM images of Fe 3 O 4 nano microspheres; (d-e) TEM images of the FBU composite material; (f) elemental distribution map; (g) XRD pattern comparison; (h) FT-IR spectrum; (i) UV-Vis absorption spectrum and band gap analysis
[0038] Figure 2 : Comparison of the degradation performance of different catalytic systems for Rhodamine B;
[0039] Figure 3 : Effect of H 2 O 2 concentration on the photo-Fenton degradation of Rhodamine B;
[0040] Figure 4 : Photo-Fenton synergistic antibacterial performance evaluation, (a) colony morphology of E. coli under different treatment conditions; (b) bar chart of the number of E. coli colonies and bar chart of sterilization efficiency.
[0041] Figure 4 The light irradiation time in the figure is 30 minutes, I) PBS; II) Fe 3 O 4 +H 2 O 2 ; III) Uio-66-NH2@BA + Light; IV) FBU + H 2 O 2 , and; V) FBU + Light, VI) FBU + H 2 O 2 + Light,.[H 2 O 2 = 10 -4 M, [FBU] = 100 μg / mL. DETAILED DESCRIPTION OF THE INVENTION
[0042] The embodiments of the present invention will be described in detail below. Although the present invention will be described and explained in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, any modifications or equivalent substitutions made to the present invention should be covered within the scope of the claims of the present invention.
[0043] In addition, for a better description of the present invention, numerous specific details are given in the following specific embodiments. Those skilled in the art will understand that the present invention can also be implemented without these specific details.
[0044] The concept of the present invention is proposed based on actual production needs. To facilitate the understanding of the technical concept of the present invention by those skilled in the art, the following further explanations are made:
[0045] In view of the problems in the background technology, the present invention proposes a core-shell structured Fe 3 O 4 / UIO-66-NH 2 @BA(FBU) heterogeneous catalyst. This material uses magnetic Fe 3 O 4 as the core, forms a heterojunction by coating with UiO-66-NH 2 metal-organic framework (MOF), and modifies the surface properties with benzoic acid (BA). The strong magnetism of Fe 3 O 4 gives the material the ability to be rapidly recovered. The high specific surface area and photoactivity of UiO-66-NH 2 broaden the light response range (to the visible light region), and the introduction of BA further optimizes the surface electronic structure of the material, promoting the separation of photo-generated carriers. Experiments show that under a 50W LED light source, the 60-minute degradation rate of Rhodamine B (RhB) in the FBU / H 2 O 2 system can reach 97.3%, and the sterilization rate against Escherichia coli reaches 99.10%. Compared with the prior art, the present invention realizes a double breakthrough in the efficiency of the photo-Fenton reaction and the stability of the catalyst through the collaborative design of components and structures, providing an efficient and low-cost technical solution for the treatment of complex wastewater.
[0046] Furthermore, the present invention belongs to the field of inorganic nanomaterials and the environment. A Fe 3 O 4 / UIO-66-NH 2 @BA composite material (abbreviated as FBU) is synthesized by a two-step solvothermal method. Specifically, it relates to a visible light-responsive photo-Fenton heterogeneous catalyst, which degrades Rhodamine B wastewater and resists Escherichia coli through an efficient photo-Fenton reaction with a 50W led as the only light source.
[0047] To this end, the present invention provides the following solutions:
[0048] A preparation method of a highly efficient and low-consumption heterogeneous catalyst based on a photo-Fenton system, comprising the following steps:
[0049] Step (a) Preparation of Fe 3 O 4 nanospheres: Dissolve FeCl 3 ·6H 2 O, Na 3 Cit·2H 2 O and NaOAc in ethylene glycol according to a mass ratio of 1.082:0.412:1.2, magnetically stir for 1 hour to form a uniform precursor, transfer it to a reaction kettle with a filling degree of 50 - 70%, react at 190 - 210 °C for 8 - 12 hours, cool, and separate the product by magnetic separation or centrifugation, wash and dry at 60 °C to obtain a powdery product;
[0050] Step (b) Preparation of Fe3O4 / UIO-66-NH2@BA composite material: Disperse the Fe3O4 nanospheres obtained in step (a) and ZrCl4 in 40 ml of DMF and ultrasonicate for 15 minutes, add NH 2 -BDC and benzoic acid and continue ultrasonication for 15 minutes, transfer to a reaction kettle and react at 130 °C for 12 hours, cool, and collect the precipitate by magnetic separation or centrifugation, wash and vacuum dry to obtain Fe3O4 / UIO-66-NH2@BA.
[0051] In the above solution, in step (a), the amount of ethylene glycol used is 40 ml, the filling degree of the reaction kettle is 60%, the reaction temperature is 200 °C, and the reaction time is 10 hours.
[0052] In the above solution, in step (b), the amount of benzoic acid used is 3 - 5 g, and the molar ratio of ZrCl 4 to NH 2 -BDC is 1:1 to 1:1.2.
[0053] The present invention also provides an application of the Fe 3 O 4 / UIO-66-NH 2 @BA heterogeneous catalyst prepared by the above method in a visible light-Fenton reaction, in the presence of a 50 W LED light source, λ≥420 nm, and H 2 O 2 for degrading organic pollutants in water bodies or inactivating bacteria.
[0054] In the above solution, the concentration of the H 2 O 2 is 1 - 20 ml / L.
[0055] In the above solution, the concentration of H 2 O 2 is 5 ml / L.
[0056] The present invention also provides a Fe 3 O 4 / UIO-66-NH 2 @BA heterogeneous catalyst, which is composed of a Fe 3 O 4 nano-microsphere core and a UIO-66-NH 2 @BA shell layer. The thickness of the shell layer is 8-12 nm, and the Zr element is uniformly distributed in the shell layer, while the Fe and O elements are concentrated in the core.
[0057] In the above solution, the catalyst has enhanced absorption in the range of 400-800 nm in the ultraviolet-visible absorption spectrum, and the band gap energy is 2.33 eV.
[0058] Example 1
[0059] Preparation of Fe 3 O 4 nano-microspheres:
[0060] Weigh FeCl3·6H2O (1.082 g), Na 3 Cit·2H 2 O (0.412 g), and NaOAc (1.2 g) with an electronic balance, then measure 40 ml of ethylene glycol and stir magnetically for 1 hour to make a uniform precursor. Load it into a high-temperature and high-pressure reaction kettle, where the filling degree of the reaction kettle is 60%, and react at 200 °C for 10 hours. After the reaction is completed and the sample is cooled, separate it with a magnet or a centrifuge, wash it three times with deionized water, and then dry it in an oven at 60 °C to obtain a powdery product.
[0061] Preparation of Fe 3 O 4 / UIO-66-NH 2 @BA photo-Fenton heterogeneous catalyst:
[0062] Add Fe 3 O 4 (200 mg) and ZrCl4 (233 mg) to 40 ml of DMF and sonicate for 15 min. Subsequently, add NH 2 -BDC (182 mg) and Benzoic Acid (4 g), continue to sonicate for 15 min, then put it into a high-temperature and high-pressure reaction kettle, heat it to 130 °C and react for 12 h. After cooling to room temperature, centrifuge or magnetically absorb and collect the precipitate, wash it three times with H 2 O, and then dry it under vacuum to obtain Fe 3 O 4 / UIO-66-NH 2 @BA。
[0063] As Figure 1 shown in (a-c), highly water-dispersible and uniformly shaped Fe 3 O 4 nanospheres with an average diameter of about 250 nm were synthesized by solvothermal method. Figure 1 As shown in (d-e), after being compounded with UiO-66-NH 2 @BA, a shell layer with an average thickness of about 10 nm was formed on the surface of Fe 3 O 4 nanospheres. The elemental distribution map of FBU ( Figure 1 (f)) shows that Fe and O elements are mainly concentrated in the core, while Zr elements are uniformly distributed in the shell. This confirms that a UiO-66-NH2 shell layer has been successfully formed on the surface of Fe 3 O 4 nanospheres.
[0064] Figure 1 (g) shows the powder X-ray diffraction (PXRD) pattern of the synthesized material. In the PXRD pattern of Fe 3 O 4 , only six characteristic peaks were observed at 2θ = 30.12°, 35.48°, 43.12°, 57.02° and 62.62°, corresponding to the (220), (311), (400), (511) and (440) crystal planes of cubic spinel Fe 3 O 4 . In addition, the XRD pattern of FBU shows characteristic peaks (<30°) matching those of UiO-66-NH 2 at 2θ = 7.16°, 8.38° and 25.59°, corresponding to the (111), (200) and (442) crystal planes of UiO-66-NH 2 . This confirms the coexistence of Fe 3 O 4 and UiO-66-NH 2 in the composite material.
[0065] To further confirm the composition of the FBU composite material, Fourier transform infrared spectroscopy (FT-IR) was used to characterize the prepared samples, and the results are as Figure 1 shown in (h). The FT-IR spectrum of Fe 3 O 4 nanoparticles shows a broad absorption band in the range of 500 - 700 cm -1 , which is attributed to the stretching vibration of the Fe-O bond. In addition, at 1370 cm -1 and 1605 cm-1 Absorption bands were observed nearby, corresponding to the asymmetric and symmetric stretching vibrations of the -COO- functional group in sodium citrate, respectively. These results indicate that Fe 3 O 4 has carboxylate anions on its surface. Compared with pure UiO-66-NH 2 @BA and Fe 3 O 4 , the characteristic absorption peaks of the FBU composite material showed a slight shift, but the main peak positions remained basically unchanged, indicating that the structural integrity of the composite material was retained. In the FBU composite material, the characteristic absorption peaks at 772, 723, and 665 cm -1 were consistent with the vibration of O-Zr-O. In addition, the absorption peaks at 1385 cm -1 , 1429 cm -1 , and 1595 cm -1 were attributed to the carboxyl groups in NH 2 -BDC and benzoic acid.
[0066] As can be seen from the ultraviolet-visible spectrum (UV-Vis) shown in (i) of Figure 1 , Fe 3 O 4 showed strong absorption in the wavelength range of 200 to 600 nm, indicating its high visible light absorption ability. In contrast, UiO-66-NH 2 @BA showed two obvious absorption peaks at 275 nm and 375 nm, which were attributed to the n-π transition of the lone pair electrons of the amino group in the NH 2 -BDC organic ligand and the absorption overlap with the Zr-O cluster. Compared with UiO-66-NH 2 @BA, the light absorption range of the composite material FBU was significantly redshifted to the visible light region, and it showed enhanced absorption performance in the wide wavelength range of 400 to 800 nm. The band gap energies of the three materials were calculated by the Kubelka-Munk equation. The band gap of Fe3O4 was 1.80 eV, the band gap of UiO-66-NH 2 was 2.84 eV, and the band gap of FBU was 2.33 eV. These results indicate that the combination of Fe 3 O 4 with UiO-66-NH 2 significantly improved the visible light absorption performance.
[0067] As Figure 2 shown, the degradation effect of RhB under different systems was evaluated. In the Vis / H 2 O 2 system, no degradation of RhB was observed, indicating that RhB was difficult to degrade naturally without a catalyst. In Vis / Fe3 O 4 / H 2 O 2 and Vis / UiO-66-NH 2 @BA / H 2 O 2 In the system, the degradation efficiencies of RhB within 60 minutes were 30.4% and 47.2% respectively. However, in the Vis / FBU / H 3 O 4 system combined with Fe 2 O 2 and UiO-66-NH 2 @BA, with only a 50W LED as the light source, the degradation efficiency of RhB reached 97.3% within 60 minutes, demonstrating the significant photo-Fenton catalytic activity of FBU. When the light was removed (FBU / H 2 O 2 system), the degradation efficiency decreased to 54.5%; when H 2 O 2 was omitted (Vis / FBU system), the degradation efficiency decreased to 65.9%. These results highlight the important roles of light and H 2 O 2 in the system and confirm that the composite material effectively enhances the photocatalytic performance.
[0068] Figure 3 The study shown investigated the effect of H 2 O 2 dosage on the degradation of RhB in the Vis / FBU / H 2 O 2 system to determine the optimal concentration ( Figure 3 ). When the concentrations of H 2 O 2 were 1, 5, 10, and 20 ml / L respectively, the degradation efficiencies of RhB were 86.5%, 97.3%, 98.4%, and 98.6% respectively. Although the highest degradation efficiency was achieved at 20 ml / L, the dosage of H 2 O 2 was four times that at 5 ml / L, while the degradation efficiency only increased by 1.3%. Therefore, it was determined that a concentration of H 2 O 2 of only 5 ml / L was sufficient to achieve the optimal degradation efficiency.
[0069] In the antibacterial study, using a 50W LED (λ≥420 nm) as the light source, the antibacterial effects of Fe 3 O 4 , UiO-66-NH 2 @BA, and FBU on Escherichia coli (E. coli) under different treatment conditions were evaluated. As Figure 4As shown, in the control group ( Figure 4 I) of part a, a large number of Escherichia coli colonies survived, indicating that the use of only a 50W LED lamp had a minimal impact on bacterial survival rate. In Fe 3 O 4 +H 2 O 2 group, weak antibacterial activity was observed, indicating that the Fenton reaction driven only by Fe 3 O 4 and low-concentration H 2 O 2 did not show significant bactericidal effects. Similarly, in the UiO-66-NH 2 @BA + light irradiation group, the antibacterial effect was slightly improved but not significant, indicating that the photocatalytic activity of UiO-66-NH 2 @BA alone was not sufficient to achieve an ideal sterilization effect. Similar results were also observed in the FBU + H 2 O 2 and FBU + light irradiation groups. However, in the FBU + H 2 O 2 + light irradiation group, compared with the control group, the number of Escherichia coli colonies decreased by 2.01 orders of magnitude, and the sterilization rate reached 99.10%. This indicates that the synergistic effect of the Fenton reaction and photocatalysis is crucial for achieving optimal antibacterial performance.
Claims
1. A method for preparing a high-efficiency and low-consumption heterogeneous catalyst based on a photo-Fenton system, characterized in that: The following steps are involved: Step (a) Preparation of Fe3O4 nanospheres: FeCl3.6H2O, Na3Ci t 2H2O and NaOAc are dissolved in ethylene glycol at a mass ratio of 1.082:(0.0516-0.0.516):1.2, and magnetically stirred for 1 hour to form a uniform precursor, which is then transferred to a reactor with a filling degree of 50-70%, reacted at 190-210°C for 8-12 hours, and after cooling, the product is separated by magnetic separation or centrifugation, washed and dried at 60°C to obtain a powdery product; Step (b) Preparation of Fe3O4 / UIO-66-NH2@BA composite material: The Fe3O4 nanospheres and ZrCl4 obtained in step (a) are dispersed in 40 ml of DMF and ultrasonicated for 15 minutes, NH2-BDC and benzoic acid are added and ultrasonicated for 15 minutes, the mixture is transferred to a reactor and reacted at 130°C for 12 hours, and the precipitate is collected by magnetic separation or centrifugation after cooling, washed and vacuum dried to obtain Fe3O4 / UIO-66-NH2@BA.
2. The method according to claim 1, characterized in that: The amount of ethylene glycol used in step (a) is 40 ml, the filling degree of the reactor is 60%, the reaction temperature is 200° C., and the reaction time is 10 hours.
3. The method according to claim 1, characterized in that: The mass ratio of Fe3O4, ZrCl4, NH2-BDC and benzoic acid in step (b) is 1:(1.1-1.3):(0.8-1.0):(18-22).
4. An application of a Fe3O4 / UIO-66-NH2@BA heterogeneous catalyst prepared by the method of any one of claims 1 to 3 in a visible light-Fenton reaction, characterized in that: Under the conditions of 50W LED light source, λ≥420nm, and H2O2, it is used to degrade organic pollutants in water or inactivate bacteria.
5. The use according to claim 4, characterized in that: The concentration of H2O2 is 1-20ml / L.
6. The use according to claim 4, characterized in that: The concentration of H2O2 is 5ml / L.
7. A Fe3O4 / UIO-66-NH2@BA heterogeneous catalyst, characterized in that: It is composed of a Fe3O4 nanosphere core and a UIO-66-NH2@BA shell layer, the shell layer thickness is 8-12nm, and the Zr element is evenly distributed in the shell layer, and the Fe and O elements are concentrated in the core.
8. The catalyst according to claim 7, characterized in that: The UV-visible absorption spectrum has enhanced absorption in the range of 400-800nm and a band gap energy of 2.33eV.